(untitled) (Aintelia Science Notes, 2022)
Container terminals are multi-component structures where different operations are carried out and also have very high investment costs. In this context, the capacity of the terminal should be well analyzed in all aspects and it should be operated in the most effective and efficient way by revealing the problems that affect the capacity negatively. There are different methods like optimum, theoretical and actual capacity for the evaluation of port capacity in the literature. Differently these concepts, the terminal capacity can also be measured by obtaining the individual capacities of the components of the port, such as berth capacity and storage area capacity. The methodology that is the subject of this study is the static and dynamic port capacity concepts developed by Lagoudis and Rice. Static capacity is related to the use of available land a appoint in time. Dynamic capacity, on the other hand, is based on the evaluation of technology of equipment and skill level of labor over a period of time. The terms of static and dynamic capacity are considered together in evaluating port capacity. In this study, the dynamic/static capacity evaluation methodology was used on a case study terminal and the results were discussed.